Avoiding Medicaid enrollment after the reversal of the changes in the public charge rule among Latino and Asian immigrants. (13th July 2022) - Bustamante, Arturo Vargas; Félix‐Beltrán, Lucía; Nwadiuko, Joseph; Ortega, Alexander N.
Abstract: Objective: To estimate the avoidance of Medicaid enrollment among Latino and Asian immigrants due to fears about immigration status. In 2019, changes to the "public charge" rule made it difficult for immigrants to receive a green card or permanent residence visa, particularly for those who used health and nutrition benefits. Despite the Biden administration's reversal of these changes, fear and misinformation persist among immigrants. Data Sources: Pooled data from the 2017 to 2020 California Health Interview Survey. Study Design: We used adjusted predicted probability models to estimate differences in access to and use of health care and health insurance coverage among Latino and Asian immigrant adults with and without green cards, using US citizens as the reference. We estimated the avoidance of Medicaid enrollment among immigrants without a green card, the immigrant population subject to the public charge rule. Data Collection/Extraction Methods: Population stratified by race/ethnicity and green card status. Principal Findings: Latino immigrants without a green card were −23.1% (CI: −27.8, −18.4) less likely to be insured, −9.2% (CI: −12.8, −5.5) less likely to have Medicaid coverage, −9.3% (CI: −14.5, −4.1) less likely to have a usual source of care, and −8.4% (CI: −13.2, −0.3) less likely to have a physician visit relative to citizens. Asian immigrants without a green card were −11.7% (CI: −19.7, −3.72) less likely to be insured, −8.8% (CI: −11.6, −6.1) less likely to have Medicaid coverage, −11.6% (CI: −19.3, −3.9) less likely to have a usual source of care, and −11.0% (CI: −19.2, −2.3) less likely to have a physician visit. Between 107, 956 and 192, 905 Latino immigrants and 1294 and 4702 Asian immigrants in California likely avoided Medicaid enrollment due to fears about their immigration status. Conclusion: While our estimates are lower than those of previous studies, our findings highlight barriers to health care for immigrants despite the reversal of the changes in the public charge rule. Since the public charge rule was not abolished, immigrants with low incomes might choose not to seek health care, despite recent efforts in California to expand Medicaid coverage to all eligible immigrants regardless of documentation statuses.